Penguatan Peran Perempuan dalam Pengawasan Partisipatif yang Berkeadilan dan Inklusif di Kabupaten Lombok Timur - Baiq Dewi Kamariani; Nur Fitri Eka Asbarini; Siti Hidayatul Jum’ah; Widya Hartati; Hartiani Hartiani; Muhammad Atha’ Iqbal (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2026)
Women's involvement in election supervision remains relatively low, despite the significant number of female voters in many regions. This condition indicates a gap between women's electoral participation as voters and their active role in ensuring fair and transparent elections. Therefore, this community service activity aims to increase women's understanding and participation in election supervision through community-based outreach and education programs. The methods used include structured outreach sessions, interactive discussions, question-and-answer forums, and the provision of educational materials related to participatory supervision and the importance of democratic accountability. This activity was carried out in East Lombok Regency with the active involvement of various women's organizations and local community groups. The results showed a noticeable increase in participants' understanding of the importance of election supervision, including their awareness of rights and responsibilities as citizens. In addition, there was a growing commitment among participants to be actively involved in supervision efforts, both individually and collectively. This program is expected to encourage more inclusive, participatory, and equitable election supervision, while also strengthening women's roles in supporting democratic processes at the local level.